Step-by-step explanation:
6/24
=1/4
;)
;(
;/
;]
;|
;[
Answer:
x = - 3
Step-by-step explanation:
Given
7(x + 2) = 2x - 1 ← distribute parenthesis on left side
7x + 14 = 2x - 1 ( subtract 2x from both sides )
5x + 14 = - 1 ( subtract 14 from both sides )
5x = - 15 ( divide both sides by 5 )
x = - 3
Answer:
3(x - 12)(x + 2)
Step-by-step explanation:
Given
3x² - 30x - 72 ← factor out 3 from each term
= 3(x² - 10x - 24) ← factor the quadratic
Consider the factors of the constant term (- 24) which sum to give the coefficient of the x- term (- 10)
The factors are - 12 and + 2 , since
- 12 × 2 = - 24 and - 12 + 2 = - 10 , thus
x² - 10x - 24 = (x - 12)(x + 2) and
3x² - 30x - 72 = 3(x - 12)(x + 2)
2/5 = y/100
40/100 = y/100
Y=40
It should be D Vietnam I believe and by the way you have this under mathematics.